Reevaluating Brand Power: The Dominant Influence of Word of Mouth and Price in Health Product Purchases - Helsi Dominggus; Prida Ariani Ambar Astuti (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2025)
The rising prevalence of diabetes in Indonesia has increased the demand for low-calorie sweetener products such as Diabetasol. However, despite ranking second in the Top Brand Index, its market share has declined over the past five years. This study aims to analyze the influence of brand image, price, and word of mouth on Diabetasol purchase decisions, with purchase intention as a mediating variable. Using a quantitative approach, data were collected through a structured questionnaire survey among members of the Indonesian Diabetes Association (PERSADIA) and analyzed using multiple linear regression, t-tests, F-tests, and the Sobel test. The results indicate that, simultaneously, the three independent variables significantly affect both purchase intention and purchase decisions. Only price and word of mouth directly affect both dependent variables; brand image has no significant direct impact. Purchase intention was found to mediate the influence of price and word of mouth on purchase decisions. These findings, analyzed based on consumer behavior and marketing communication theories, highlight the importance of pricing strategies aligned with perceived value and leveraging consumer testimonials to strengthen purchase decisions.